THE IMPACTS OF CODE-MIXING FOR MALAY NATIVE SPEAKER - Kartini Rahmatillah (ETERNAL (English Teaching Journal), 2012)
The use of code-mixing, especially for English Code-Mixing, by Malay Kuala Lumpur Native Speaker, becomes the main issue in this research. Thus through this research, it will be found out the reasons for this language error happens, the impacts for using the code-mixing, in terms of sociolinguistic view. The sample limitation is only 10 (ten) people of Malay Kuala Lumpur native speaker, who are randomly selected.  The research is a case study and descriptive qualitative research, which arises the issue of the use of code-mixing among the Malay Kuala Lumpur native speaker who are taking their study in Indonesia. Data are collected through observation to samples which are also as the population.  Through the brief observation it can be concluded that the use of code-mixing because of usual habit of using English among the respondents, added by the fact that English is also their second language which is widely spoken in daily bases or in formal bases. The use of English Code-mixing is also for the need to highlight the speaker in terms of they will be looked as an intellectual and elite people. The impact of using code-mixing cannot be confirmed that it brings a negative effect, but it is not possible that the existence and even the use of Malay language can be slowly moved among their own native speaker.